The rhetoric of manipulation unmasking semantic perversions - Harvey, Robert 1951- (Bloomsbury Academic, 2025)
"A provocative and timely look at how language is used to manipulate the truth, how our gullibility leaves us susceptible to manipulation, and what we can do to reverse these trends. The Rhetoric of Manipulationlooks behind the curtain of political and social communications in the age of "fake news" and the "post-truth" to show how the perversely engineered semantics at work today shapes culture and undermines reality. While language has always been manipulated to direct or anesthetize thought, today’s semantic perversions orient opinion and subdue political action to an alarming degree. Under such conditions, we are particularly susceptible to demagoguery. Arguing that too many of us have let our critical faculties wither, Robert Harvey opens our ears and eyes to an insidious impediment to free thinking by unflinchingly examining five realms of semantic perversion: the contemporary vocabulary of war; the recently evolved language tool known as scare quotes; the terms used to peddle white supremacy; the phenomenon of so-called cancel culture; and the jargon deployed in the corporatization of higher education. The wager ofThe Rhetoric of Manipulationis that a frank exposé of bad faith discursive practices and our accompanying gullibility can contribute to reversing the trend, remedying the current situation in view of a far more ethical immediate future, and remediating some of the damage already done."
Informationen wurden der Landingpage entnommen, da weder Titelseite noch Impressum vorhanden (Bloomsbury Collections)